Friction material of composite brake pad and composite brake pad

By using modified vermiculite powder in the friction material of the synthetic gate sheet to form the grid space, the problem of deformation and abrasion of the synthetic gate sheet at high temperature is solved, extending the service life and improving the braking effect.

CN119119602APending Publication Date: 2024-12-13ZHEJIANG LEFEN RAIL TRANSIT TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411200128.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The friction material of the synthetic gate plate is prone to deform at high temperatures, resulting in reduced braking effect, local hot spots and abrasion, and shortened service life.

Method used

Using a friction material containing modified vermiculite powder, the vermiculite powder is expanded to form a grid space during the thermal curing process, reducing the compression modulus and improving the bonding strength, and combining rubber materials to maintain friction performance.

Benefits of technology

It extends the service life of the synthetic brake pad, improves the braking effect, avoids local hot spots and abrasion, and ensures the hardness and compression strength of the friction material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119602A_ABST
    Figure CN119119602A_ABST
Patent Text Reader

Abstract

The friction material is prepared from the following raw materials in parts by mass: 30 to 45 parts of nitrile rubber, 10 to 15 parts of polyimide resin, 10 to 20 parts of mineral fiber, 2 to 4 parts of carbon fiber, 3 to 5 parts of aramid fiber, 1 to 2 parts of rubber vulcanization accelerator, 10 to 20 parts of friction modifier and 5 to 8 parts of modified vermiculite powder. The modified vermiculite powder is obtained by loading sulfur on gaps on the surface and between layers of raw vermiculite powder, and the particle size of the modified vermiculite powder is 200-300nm; a regulation stage exists in thermocuring of the friction material, and the temperature of a friction material precursor in the regulation stage is 300-310 DEG C, so that the synthetic brake pad friction material has the properties of low compression modulus, proper hardness and good compression strength, and the prepared synthetic brake pad is long in service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to train braking, and in particular to a friction material of a synthetic brake pad and a synthetic brake pad. Background Art

[0002] As train speeds increase, the current train braking method has largely changed from tread braking to disc braking. Disc braking relies on the contact friction between the brake pad and the friction surface of the brake disc to generate braking force.

[0003] Among the existing brake pads, synthetic brake pads are a hot research direction. The friction material used by synthetic brake pads to rub against the brake disc is a material that is mainly composed of rubber, resin, and fiber, with no or a small amount of metal powder mixed and then pressurized, heated, and solidified for braking. Compared with gray cast iron friction materials and aluminum alloy friction materials, it has the advantages of light weight and low braking noise.

[0004] However, the heat resistance of synthetic brake pads is lower than that of gray cast iron and aluminum alloy. In a large number of sample tests and loss parts recovery inspections, local black spots or more prominent abrasion than other areas were found on the friction surface. The observation of brake pads during the braking process with an infrared camera found that local hot spots often appeared in local black spots and prominent abrasion areas in the test samples, that is, the local temperature was higher than the surrounding temperature. After further analysis, apart from the inevitable deviations and mixing technology during the installation process, from the perspective of material properties, the main reason is that when the material takes into account other properties, the friction material will inevitably deform at high temperatures, and the compression modulus of the friction material is too large, resulting in the friction material and the brake disc not being flat, so local hot spots are easily generated during the braking process, resulting in local black spots and prominent abrasion areas. This problem will lead to a decrease in braking effect, and it is easy to extend and develop into thermal cracks in the future, which will advance the replacement time of the friction material and reduce the service life of the synthetic brake pad. Summary of the invention

[0005] In order to ensure the braking effect of a synthetic brake pad and extend the service life of the synthetic brake pad, a friction material of a synthetic brake pad and a synthetic brake pad are provided.

[0006] The above first invention objective of the present invention is achieved through the following technical solutions: A friction material for a synthetic brake pad comprises the following raw materials in parts by mass: 30-45 parts of nitrile rubber, 10-15 parts of polyimide resin, 10-20 parts of mineral fiber, 2-4 parts of carbon fiber, 3-5 parts of aramid fiber, 1-2 parts of rubber vulcanization accelerator, 10-20 parts of friction regulator, and 5-8 parts of modified vermiculite powder. The modified vermiculite powder is obtained by loading sulfur on the surface of raw vermiculite powder and in the gaps between layers, and the particle size of the modified vermiculite powder is 200-300 nm; There is an adjustment stage in the thermal curing of the friction material, and the temperature of the friction material precursor is 300-310°C in the adjustment stage.

[0007] By adopting the above technical solution, polyimide resin is added to adjust the toughness and heat resistance of nitrile rubber, mineral fiber, carbon fiber and aramid fiber are heated to improve the high temperature deformation resistance of friction materials, friction modifier is added to adjust the friction coefficient to ensure the braking effect, and modified vermiculite powder is added on this basis, and an adjustment stage is set during its preparation; Modified vermiculite powder is based on raw vermiculite powder. When raw vermiculite is heated, the water in the gaps between its internal layers will evaporate. When the temperature reaches a certain level, separation, error and expansion of the layers will occur, which will eventually manifest as the "growth" expansion of the raw vermiculite on the C axis of the crystal layer. When the temperature is lower than 150°C, the raw vermiculite layers are difficult to expand due to insufficient pressure. When the temperature is higher than 200°C, the raw vermiculite will expand at different temperatures and reach the maximum value at different temperatures according to the scale size and thickness of the raw vermiculite or the particle size of the raw vermiculite powder. The smaller the scale size and thickness of the raw vermiculite or the particle size of the raw vermiculite powder, the lower the temperature at which the expansion occurs. The particle size of the raw vermiculite powder in the modified vermiculite powder in the present application is less than 1 mm, and the sulfur in the gap between the layers hinders the discharge of water vapor from the gap between the layers, promoting the increase of the pressure in the gap between the layers. Therefore, when the modified vermiculite powder in the present application is heated to 280-300°C under normal pressure, it expands, and the expansion multiple is 3.2-3.5 times. During the adjustment stage of the friction material of the present application, the modified vermiculite powder expands, and the interlayers of the vermiculite expand. As for the friction material, a large number of grid spaces supported by the expanded vermiculite are formed inside the friction material due to the change of the vermiculite powder particles. At the same time, due to the expansion of vermiculite powder, the gap between the layers is opened, the gap is enlarged, and the sulfur on the gap wall is exposed. After the friction material finishes the adjustment stage, the rubber material outside the vermiculite powder actively shrinks toward the vermiculite and fits closely with its surface, and is tightly combined and hardened quickly under the action of sulfur, so as to prevent the expanded vermiculite from being squeezed and crushed during the cooling process, and keep the grid space in the friction material; These grid spaces reduce the compression modulus of the friction material while reducing the hardness and compression strength less, so as to deal with the problem of black spots and local abrasion of the friction material under high temperature deformation. In addition, the rubber material fits tightly with the outer surface of the expanded vermiculite powder and has sufficient bonding strength, which can also improve the braking performance of the friction material to a certain extent. The synthetic brake pad friction material has the properties of low compression modulus, suitable hardness and good compression strength, and the synthetic brake pad obtained has a long service life.

[0008] Optional: The preparation method of the modified vermiculite powder is as follows: The raw vermiculite is washed and crushed to obtain the vermiculite raw body; The vermiculite body is soaked in a 32.4-35.4wt% sodium sulfite solution for 8 hours, filtered out, and after the surface is drained, stirred at 54±2°C in a hydrogen sulfide atmosphere. After the vermiculite body changes color, it is cooled and the reaction material is washed with clean water to obtain modified vermiculite powder.

[0009] By adopting the above technical scheme, sodium sulfite is penetrated into the gaps between the layers of vermiculite by soaking, and then dried in a hydrogen sulfide atmosphere, hydrogen sulfide is dissolved in the water in the gaps between the vermiculite layers and reacts with sodium sulfite to be converted into sulfur. By controlling the concentration of the sodium sulfite solution appropriately, modified vermiculite powder can be quickly and efficiently obtained.

[0010] Optionally, the vermiculite body is treated with acid leaching, water leaching to remove the acid, and then immersed in a sodium sulfite solution.

[0011] By adopting the above technical scheme, after the vermiculite body is acid-washed, the debris at the edge of the gap between the layers is washed away, and the surface of the vermiculite body and the wall surface at the edge of the gap between the layers are activated by the acid, so that the sodium sulfite is easier to penetrate, and the sulfur settles more and deeper in the gap between the layers of the vermiculite body, which is beneficial to the expansion of the modified vermiculite powder at a lower temperature and can improve the bonding strength between the modified vermiculite powder and the rubber, further reduce the compression modulus at the original hardness, reduce the black spots and local abrasion of the friction material when it is used, and extend the service life of the friction material.

[0012] Optionally, the acid solution used in the acid leaching treatment is a 2.4-3.6wt% sulfuric acid solution.

[0013] By adopting the above technical scheme, when the 2.4-3.6wt% sulfuric acid solution realizes the acid leaching effect, the corrosion loss on the C axis of the vermiculite original body crystal is small, thereby ensuring the beneficial effect brought by the expansion of the modified vermiculite powder.

[0014] Optionally: the friction modifier is molybdenum disulfide.

[0015] By adopting the above technical solution, molybdenum disulfide has better compatibility with rubber than other inorganic friction regulators, and while adjusting the friction performance, the increase in compression modulus is less.

[0016] Optionally: the particle size of the molybdenum disulfide is 0.5 to 2.5 μm.

[0017] By adopting the above technical solution, molybdenum disulfide at this particle size can better regulate the friction performance of the friction material.

[0018] Optionally, the mineral fiber is basalt fiber.

[0019] By adopting the above technical solution, basalt fiber has good heat resistance and has a good effect on improving the wear resistance of friction materials.

[0020] The above second invention objective of the present invention is achieved through the following technical solutions: A synthetic brake pad comprises a steel back and a friction piece formed by solidifying the synthetic brake pad friction material.

[0021] By adopting the above technical solution, when the composite brake pad of the present application is braked, the friction material and the brake disc are closely attached, black spots are not easily generated or local abrasion is aggravated, the service life is long, and the braking effect is good.

[0022] In summary, this application has at least the following beneficial effects: 1. Synthetic brake pad friction material has the properties of low compression modulus, suitable hardness and good compression strength; 2. When the composite brake pad of the present application is used for braking, the friction material and the brake disc are closely attached, black spots are not easily generated or local abrasion is aggravated, the service life is long, and the braking effect is good. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 It is a schematic diagram of the structure of the composite brake pad.

[0024] Reference numerals: 1. Steel back; 2. Friction parts. DETAILED DESCRIPTION

[0025] raw material: Raw materials not further described in this application are commercially available products. Some product parameters and information are as follows: The nitrile rubber is Japan Zeon NBR nitrile rubber DN4580; The polyimide resin is PI300 product of Changzhou Yaan New Materials Co., Ltd.; There are two types of mineral fibers: basalt fiber and glass fiber, both of which are 1.5 cm in length and 20 μm in diameter.

[0026] The carbon fiber is chopped carbon fiber with a length of 1.5 cm and a diameter of 6 μm, which is obtained by shearing with TZ300 produced by Weihai Guangwei Composite Materials Co., Ltd.

[0027] The aramid fiber is 1414 para-aramid fiber with a diameter of 17 μm and a length of 6 mm, and is the FL002 product of Shenzhen Teli New Materials Technology Co., Ltd.

[0028] The rubber vulcanization accelerator is accelerator CZ, and its chemical name is N-cyclohexyl-2-benzothiazole sulfenamide.

[0029] Preparation Example 1 A modified vermiculite powder, the preparation method of which is as follows: The raw vermiculite is washed and crushed to obtain vermiculite with a particle size of 200 nm; The vermiculite body was subjected to acid leaching treatment, the acid used was 3.6wt% sulfuric acid, and the leaching time was 10min; After the acid leaching is completed, the vermiculite body is filtered and transferred to water for leaching and acid removal. After the pH of the residual water on the surface of the vermiculite is greater than 6.8, the vermiculite body is filtered and the surface water is drained to obtain the acidified vermiculite body; 2 kg of acidified vermiculite original body was soaked in 35.4 wt% sodium sulfite solution for 8 hours, filtered out, and after the surface was drained, stirred for 3 hours at 54±2°C (±2°C here is the normal fluctuation of the equipment at the set value of 54°C, not the adjustment range) and hydrogen sulfide atmosphere (30 vol% H2S, 70 vol% Ar) until the acidified vermiculite original body changed color. The solution was cooled to room temperature, and the reaction material was washed with clean water. After filtering, it was naturally dried and sieved to obtain modified vermiculite powder.

[0030] Preparation Example 2 A modified vermiculite powder, which is different from Preparation Example 1, is prepared as follows: The raw vermiculite is washed and crushed to obtain vermiculite with a particle size of 250 nm; 2 kg of vermiculite original body was soaked in 35.4 wt% sodium sulfite solution for 8 hours, filtered out, and after the surface was drained, stirred for 3 hours at 54±2°C (here ±2°C is the normal fluctuation of the equipment at the set value of 54°C, not the adjustment range) and hydrogen sulfide atmosphere (30 vol% H2S, 70 vol% Ar) until the vermiculite original body changed color. The solution was cooled to room temperature, and the reaction material was washed with clean water. After filtering, it was naturally dried and sieved to obtain modified vermiculite powder.

[0031] Preparation Example 3 A modified vermiculite powder is different from that of Preparation Example 2 in that the vermiculite raw body is screened with a particle size of 300 nm.

[0032] Preparation Example 4 A modified vermiculite powder is different from that of Preparation Example 2 in that the particle size of the vermiculite raw body screened is 2 mm.

[0033] Preparation Example 5 A modified vermiculite powder is different from that of Preparation Example 2 in that the vermiculite raw body is screened and used with a particle size of 50 μm.

[0034] Preparation Example 6 A modified vermiculite powder is different from Preparation Example 1 in that the concentration of the sodium sulfite solution is 10.4wt% and the soaking time is 16h.

[0035] Preparation Example 7 A modified vermiculite powder is different from Preparation Example 1 in that the concentration of the sodium sulfite solution is 20.4wt% and the soaking time is 8h.

[0036] Preparation Example 8 A modified vermiculite powder is different from Preparation Example 1 in that the concentration of the sodium sulfite solution is 32.4wt% and the soaking time is 8h.

[0037] Preparation Example 9 A modified vermiculite powder is different from Preparation Example 1 in that the concentration of the sodium sulfite solution is 42.4wt% and the soaking time is 8h.

[0038] Preparation Example 10 A modified vermiculite powder is different from the one prepared in Example 1 in that the concentration of sulfuric acid used in the acid leaching treatment of the vermiculite original body is 2.4 wt %.

[0039] Preparation Example 11 A modified vermiculite powder is different from the one prepared in Example 1 in that the concentration of sulfuric acid used in the acid leaching treatment of the vermiculite original body is 6.5 wt %.

[0040] Preparation Example 12 A modified vermiculite powder is different from the one prepared in Example 1 in that the concentration of sulfuric acid used in the acid leaching treatment of the vermiculite original body is 12.5 wt %.

[0041] Example 1 A friction material for a synthetic brake pad uses nitrile rubber, polyimide resin, mineral fiber, carbon fiber, aramid fiber, rubber vulcanization accelerator, friction regulator, and modified vermiculite powder as raw materials.

[0042] The mineral fiber is basalt fiber, the rubber vulcanization accelerator is, the friction regulator is, and the modified vermiculite powder is prepared in Preparation Example 1.

[0043] The preparation method of the friction material is as follows: S1: 4.2 kg of aramid fiber was crushed in a crusher, and 17.5 kg of molybdenum disulfide was added during the crushing process to obtain a first material; S2: The first material and 43 kg of nitrile rubber, 13.1 kg of polyimide resin, 17 kg of mineral fiber, 3.4 kg of carbon fiber, 1.6 kg of rubber vulcanization accelerator, and 7 kg of modified vermiculite powder were kneaded together in an internal mixer for 10 min at a temperature of 42° C. and a pressure of 0.4 MPa to obtain a flaky material, which was then crushed by a granulator to obtain a second material with a diameter of 10 mm; S3: 460 g of the second material is used as one portion, each portion is pressed into shape in a mold at a heating temperature of 60° C., and then heated and cured. The heating and curing is divided into three stages; The first stage is the preheating stage, the temperature of the preheating stage is 90℃, and the preheating stage time is 5 minutes; The second stage is the adjustment stage, the temperature of the adjustment stage is 310℃, and the adjustment stage time is 1min; The heating time from the preheating stage to the adjustment stage is 4 minutes; The third stage is the full curing stage, the temperature of the full curing stage is 220℃, and the time of the full curing stage is 30h. The temperature holding time from the adjustment stage to the full curing stage is 8 minutes; After the full curing stage is completed, the friction material is air cooled to room temperature to obtain.

[0044] In actual production, during the S3 stage of pressing and molding, the second material is put into the mold together with the steel back of the composite brake pad and pressed together, and the second material is temporarily fixed on the steel back. After vulcanization and curing, the friction material is more reliably fixed on the steel back.

[0045] Example 2 A friction material for a synthetic brake pad, which differs from Example 1 in that the modified vermiculite powder is prepared in Preparation Example 2.

[0046] Example 3 A friction material for a synthetic brake pad, which differs from Example 1 in that the modified vermiculite powder is prepared in Preparation Example 3.

[0047] Comparative Example 1 A friction material for a synthetic brake pad, which differs from Example 1 in that it uses nitrile rubber, polyimide resin, mineral fiber, carbon fiber, aramid fiber, rubber vulcanization accelerator, and friction modifier as raw materials.

[0048] The amount of modified vermiculite powder used in step S2 of the preparation method is 0.

[0049] Comparative Example 2 A friction material for a synthetic brake pad, which differs from Example 1 in that it uses nitrile rubber, polyimide resin, mineral fiber, carbon fiber, aramid fiber, rubber vulcanization accelerator, friction regulator, and vermiculite powder as raw materials.

[0050] The preparation method of raw vermiculite powder is as follows: The raw vermiculite is washed and crushed, and the powder with a size of 250 nm is selected as the raw vermiculite powder.

[0051] In step S2 of the preparation method, 7 kg of raw vermiculite powder is used to replace 7 kg of modified vermiculite powder.

[0052] Comparative Example 3 A friction material for a synthetic brake pad, which differs from Example 1 in that it uses nitrile rubber, polyimide resin, mineral fiber, carbon fiber, aramid fiber, rubber vulcanization accelerator, friction regulator, and modified cooked vermiculite powder as raw materials.

[0053] The preparation method of modified cooked vermiculite powder is as follows: The raw vermiculite is washed and crushed to obtain vermiculite with a particle size of 250 nm; The vermiculite body is heated to 320°C and kept at this temperature for 30 seconds to obtain heated vermiculite; 2 kg of heated vermiculite was soaked in a 35.4 wt% sodium sulfite solution for 8 h, filtered out, and after the surface was drained, stirred for 3 h at 54 ° C in a hydrogen sulfide atmosphere (30 vol% H2S, 70 vol% Ar) until the vermiculite changed color. The mixture was cooled to room temperature, and the reaction material was washed with clean water. After filtering, it was naturally dried and sieved to obtain modified cooked vermiculite powder.

[0054] In step S2 of the preparation method, 7 kg of modified cooked vermiculite powder is used to replace 7 kg of modified vermiculite powder.

[0055] Comparative Example 4 A friction material for a synthetic brake pad, which differs from Example 2 in that the modified vermiculite powder is prepared in Preparation Example 4.

[0056] Comparative Example 5 A friction material for a synthetic brake pad, which differs from Example 2 in that the modified vermiculite powder is prepared in Preparation Example 5.

[0057] Comparative Example 6 A friction material for a synthetic brake pad, which differs from Example 2 in that the temperature in the adjustment stage is 250°C.

[0058] Example 4 A friction material for a synthetic brake pad, which differs from Example 2 in that the temperature in the adjustment stage is 300°C.

[0059] Detection The friction materials obtained in Examples 1 to 4 and Comparative Examples 1 to 6 were tested for hardness, compression modulus, compression strength, and 120 km / h braking friction coefficient, and the test method was based on the test method and parameters specified in "TB3118-Railway Vehicle Composite Brake Pads" and the test method in the corresponding referenced standard in "TB3118-Railway Vehicle Composite Brake Pads". The test results are shown in the table below.

[0060] Table 1. Test results of Examples 1 to 4 and Comparative Examples 1 to 6 Hardness HHR <![CDATA[Compression modulus kJ / m 2 > Compression strength MPa 120km / h Braking Friction Coefficient Example 1 44 321 42 0.463 Example 2 44 361 42.6 0.458 Example 3 45 385 43.1 0.448 Example 4 44 373 42.9 0.45 Comparative Example 1 45 428 45.2 0.421 Comparative Example 2 42 405 38.3 0.418 Comparative Example 3 45 413 43.1 0.427 Comparative Example 4 40 386 35.8 0.432 Comparative Example 5 42 380 37.6 0.432 Comparative Example 6 45 429 45 0.418 As shown in Table 1, in Example 2, modified vermiculite powder is added as part of the raw materials, and an adjustment stage is added in the heat curing step to promote the expansion of the modified vermiculite powder. For the friction material, a large number of grid spaces supported by the expanded vermiculite are formed inside the modified vermiculite powder due to the change of the modified vermiculite powder particles; at the same time, due to the expansion of the modified vermiculite powder, the gap between the layers is opened, the gap is enlarged, and the sulfur on the gap wall is exposed. After the friction material ends the adjustment stage, the rubber material outside the modified vermiculite powder actively shrinks toward the modified vermiculite powder and fits closely with the surface, and is tightly combined and hardened quickly under the action of sulfur, so that the expanded modified vermiculite powder is prevented from being squeezed and crushed during the cooling process, and the grid space is kept in the friction material; these grid spaces make the friction material Example 2 have a lower compression modulus while the hardness and compression strength are less reduced than that of the comparative example 1; In Comparative Example 2, raw vermiculite powder is used to replace modified vermiculite powder. The raw vermiculite powder also expands in the adjustment stage, but after the adjustment stage, the grid space is partially damaged by the compression of the shrinking nitrile rubber, and the compression modulus decreases less than that in Example 2. At the same time, since the gap wall between the layers expanded after the raw vermiculite powder expands has poor bonding with the nitrile rubber, the gap between the layers cannot be supported by the organic phase mainly composed of nitrile rubber, and the mechanical properties of the friction material reflect that the compression strength decreases significantly; In Comparative Example 3, modified cooked vermiculite powder is used to replace modified vermiculite powder. However, the modified cooked vermiculite powder that has expanded during the mixing process is squeezed and further broken or compressed, and the grid space collapse is reduced, so its compression modulus decreases less than that in Example 2. It can be seen that the friction material of the present application adds modified vermiculite powder as part of the raw materials, and at the same time adds an adjustment stage in the thermal curing step, which can effectively reduce the compression modulus more while reducing the hardness and compression strength less, so as to cope with the problems of black spots and aggravated local abrasion of the friction material under high temperature deformation, and the rubber material is tightly fitted to the outer surface of the expanded modified vermiculite powder and has sufficient bonding strength, which can also improve the braking performance of the friction material to a certain extent.

[0061] By comparing Example 1 and Example 2, it can be seen that Example 1 further reduces the compression modulus compared with Example 2 under the condition of similar compression strength. The reason is that during the acid leaching process, the debris at the edge of the gap between the layers of vermiculite is washed away, the gap wall between the layers is activated, the sodium sulfite is easier to penetrate, the sulfur settles more and deeper in the gap between the layers of the vermiculite original body, and the expanded organic phase is easier to fill in the open gap and solidify, which can reduce the compression modulus more at the original hardness, reduce the black spots and local abrasion of the friction material when it is used, and extend the service life of the friction material.

[0062] In addition, the particle size of the modified vermiculite powder and the temperature in the adjustment stage in the present application are also key factors affecting the effectiveness of the modified vermiculite powder.

[0063] Here, the influence of different benefits of acid leaching treatment on particles of different small sizes is avoided, and Examples 2-3 and Comparative Examples 4-5 are compared.

[0064] By comparing Example 2 and Comparative Example 4, it can be seen that the compression modulus of Comparative Example 4 decreases far less than that of Example 2, but the compression strength of Comparative Example 4 decreases significantly. This is because the particle size of the modified vermiculite powder in Comparative Example 4 is too large, and its expansion difficulty is relatively high. At the same time, the grid space formed in the friction material after the expansion of a single modified vermiculite powder is too large, and the uneven internal stress of the friction material causes a significant decrease in the compression strength. Therefore, the particle size of the modified vermiculite powder in this application is also one of the keys to its gain effect.

[0065] In combination with Comparative Examples 4-5 and Examples 2-3, it can be seen that Comparative Example 5 is improved over Comparative Example 4, but does not show a more significant benefit. Therefore, the particle size of the modified vermiculite powder in this application needs to be 200-300 nm.

[0066] By comparing Example 2, Example 4, Comparative Example 1, and Comparative Example 6, it can be seen that although Comparative Example 6 uses the modified vermiculite powder of Preparation Example 1 like Example 1, the temperature of the adjustment stage of Comparative Example 6 is lower, and the modified vermiculite powder fails to expand effectively. The compression modulus and compression strength of Comparative Example 6 are similar to those of Comparative Example 1. Therefore, the modified vermiculite powder is pre-made to play a role in this application, and the temperature of the adjustment stage should be 300-310°C.

[0067] Example 5 A friction material for a synthetic brake pad, which differs from Example 1 in that the modified vermiculite powder is prepared in Preparation Example 6.

[0068] Example 6 A friction material for a synthetic brake pad, which differs from Example 1 in that the modified vermiculite powder is prepared in Preparation Example 7.

[0069] Example 7 A friction material for a synthetic brake pad, which differs from Example 1 in that the modified vermiculite powder is prepared in Preparation Example 8.

[0070] Example 8 A friction material for a synthetic brake pad, which differs from Example 1 in that the modified vermiculite powder is prepared in Preparation Example 9.

[0071] Example 9 A friction material for a synthetic brake pad, which differs from Example 1 in that the modified vermiculite powder is prepared in Preparation Example 10.

[0072] Example 10 A friction material for a synthetic brake pad, which differs from Example 1 in that the modified vermiculite powder is prepared in Preparation Example 11.

[0073] Embodiment 11 A friction material for a synthetic brake pad, which differs from Example 1 in that the modified vermiculite powder is prepared in Preparation Example 12.

[0074] Example 12 A friction material for a synthetic brake pad, which differs from Example 1 in that the friction modifier is zirconium dioxide with a particle size of 1.5 μm.

[0075] Embodiment 13 A friction material for a synthetic brake pad, which differs from Example 1 in that the friction modifier is 0.1 μm molybdenum disulfide.

[0076] Embodiment 14 A friction material for a synthetic brake pad, which differs from Example 1 in that the friction modifier is 0.5 μm molybdenum disulfide.

[0077] Embodiment 15 A friction material for a synthetic brake pad, which differs from Example 1 in that the friction modifier is 2.5 μm molybdenum disulfide.

[0078] Example 16 A friction material for a synthetic brake pad, which differs from Example 1 in that the friction modifier is 8 μm molybdenum disulfide.

[0079] Embodiment 17 A friction material for a synthetic brake pad, which differs from Example 1 in that the mineral fiber is glass fiber.

[0080] Embodiment 18 A friction material for a synthetic brake pad, which differs from Example 1 in that the raw materials used are 3kg aramid fiber, 10kg molybdenum disulfide, 30kg nitrile rubber, 10kg polyimide resin, 10kg mineral fiber, 2kg carbon fiber, 1kg rubber vulcanization accelerator, and 5kg modified vermiculite powder.

[0081] Embodiment 19 A friction material for a synthetic brake pad, which differs from Example 1 in that the raw materials used are 5kg aramid fiber, 20kg molybdenum disulfide, 45kg nitrile rubber, 15kg polyimide resin, 20kg mineral fiber, 4kg carbon fiber, 2kg rubber vulcanization accelerator, and 8kg modified vermiculite powder.

[0082] The friction materials obtained in Examples 5 to 19 were tested for hardness, compression modulus, compression strength, and 120 km / h braking friction coefficient. The test results are shown in the following table.

[0083] Table 2. Test results of Examples 5 to 19 Hardness HHR <![CDATA[Compression modulus kJ / m 2 > Compression strength MPa 120km / h Braking Friction Coefficient Example 5 45 346 42.5 0.445 Example 6 45 336 42.2 0.457 Example 7 45 322 42 0.456 Example 8 44 352 42.8 0.455 Example 9 45 329 42.1 0.457 Example 10 45 339 41.6 0.444 Embodiment 11 45 342 40.9 0.44 Example 12 44 328 41.1 0.454 Embodiment 13 42 315 39.5 0.428 Embodiment 14 44 320 40.9 0.441 Embodiment 15 45 334 41.4 0.452 Example 16 44 345 42.2 0.436 Embodiment 17 43 320 41 0.435 Embodiment 18 44 335 41.7 0.448 Embodiment 19 43 341 41.9 0.459 The concentration and immersion time of sodium sulfite during the preparation process of modified vermiculite powder affect its penetration into the gaps between vermiculite layers. As the concentration increases, the penetration rate increases, and as the immersion time increases, the penetration depth increases. In addition, the opening of the gaps between the layers after the vermiculite expands is affected by the expansion ratio, that is, the temperature in the adjustment stage. It is determined that the opening of the gaps between the layers after the vermiculite expands at the temperature in the adjustment stage is limited. The penetration depth of sodium sulfite in the gaps between the layers has a threshold for improving the combination of the modified vermiculite powder and the organic phase.

[0084] By comparing Example 1 with Examples 5 to 8, it can be seen that the concentrations of the sodium sulfite solutions used for the modified vermiculite powders in Examples 6, 7, 1, and 8 are increased successively. In the test results, the decrease in compression modulus and the weakening of compression strength in Example 1 are optimally balanced. In Example 8, the modified vermiculite powder has too much sulfur content, resulting in the surrounding nitrile rubber hardness and strength increasing too fast when it has not reached the adjustment stage, resulting in limited expansion of the modified vermiculite powder.

[0085] In addition, it can be seen from Example 1 and Example 5 that at a lower concentration of the sodium sulfite solution, the penetration depth can be increased by extending the immersion time, but it is not as good as increasing the concentration of the sodium sulfite solution in terms of benefits and costs. Therefore, the concentration of the sodium sulfite solution in this application is selected to be 32.4-35.4wt%, and the immersion time is 8h.

[0086] The present application studies the process parameters of the acid leaching process of the vermiculite body, wherein the concentration of the acid used for pickling affects the activation effect of the vermiculite body and the corrosion of the C axis of the vermiculite body crystal, resulting in a reduced expansion ratio and poor support strength after expansion. Combining the test results of Example 1 and Examples 9 to 11, it can be seen that Example 1 and Example 9 in the present application retain higher compression strengths under similar or lower compression moduli than Examples 10 to 11; not only does the compression modulus of Examples 10 to 11 decrease less, but the compression strength of Examples 10 to 11 also decreases greatly.

[0087] Therefore, in the present application, the sulfuric acid concentration of the vermiculite body during acid leaching is preferably 2.4-3.6 wt %.

[0088] By comparing Example 1 and Example 12, when the same mass of friction modifier is used, the compression modulus of Example 1 using molybdenum disulfide is lower than that of Example 12, and the compression strength and friction coefficient of Example 1 are greater than those of Example 12. Therefore, molybdenum disulfide is preferably used as the friction modifier in this application, which has less increase in compression modulus while adjusting the friction properties of the friction material, and is more in line with the requirements of synthetic brake pads.

[0089] The particle size selection of molybdenum disulfide affects its effect on the friction coefficient and compression modulus of the friction material. Combining Example 1 and Examples 13 to 16, it can be seen that in Example 1 and Examples 14 to 15, the requirements for a larger friction coefficient and a smaller compression modulus of the friction material are optimally met. Therefore, the molybdenum disulfide particle size selected in this application is preferably 0.5 to 2.5 μm.

[0090] Combining Example 1 and Example 17, it can be seen that basalt fiber is heat-resistant and has good flexibility. When basalt fiber is selected as the mineral fiber, the friction coefficient of the friction material is higher and the compression modulus is smaller.

[0091] In combination with Example 1 and Examples 18 to 19, it can be seen that when the mass fraction of the raw materials used in the present application is within the range, the compressible modulus is low, the hardness is suitable, and the compressive strength is good, and the obtained synthetic brake pad has a long service life.

[0092] Embodiment 20 As attached Figure 1 As shown, a composite brake pad comprises a steel back 2 and a friction member 2. The steel back is in the shape of a strip, and the friction member 2 is fixed on one side of the steel back by heat curing and vulcanization of a friction material in one of embodiments 1 to 19.

[0093] The friction member 2 of the synthetic brake pad has good compression strength and low compression modulus. During braking, the friction member 2 fits tightly to the brake disc, and is not prone to black spots or local aggravated abrasion. The synthetic brake pad has a long service life and good braking effect.

[0094] This specific embodiment is only an explanation of the present invention, and it is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to this embodiment as needed, but as long as it is within the scope of protection required by the present invention, it will be protected by the patent law.

Claims

1. A friction material for a synthetic brake pad, characterized in that: The invention comprises the following raw materials in parts by weight: 30-45 parts of nitrile rubber, 10-15 parts of polyimide resin, 10-20 parts of mineral fiber, 2-4 parts of carbon fiber, 3-5 parts of aramid fiber, 1-2 parts of rubber vulcanization accelerator, 10-20 parts of friction regulator, 5-8 parts of modified vermiculite powder, The modified vermiculite powder is obtained by loading sulfur on the surface of raw vermiculite powder and in the gaps between layers, and the particle size of the modified vermiculite powder is 200-300 nm; There is an adjustment stage in the thermal curing of the friction material, and the temperature of the friction material precursor is 300-310° C. in the adjustment stage.

2. A synthetic brake pad material according to claim 1, characterized in that: The preparation method of the modified vermiculite powder is as follows: The raw vermiculite is washed and crushed to obtain the vermiculite raw body; The vermiculite body is soaked in a 32.4-35.4wt% sodium sulfite solution for 8 hours, filtered out, and after the surface is drained, stirred at 54±2°C in a hydrogen sulfide atmosphere. After the vermiculite body changes color, it is cooled and the reaction material is washed with clean water to obtain modified vermiculite powder.

3. A synthetic brake pad material according to claim 2, characterized in that: The vermiculite body is treated by acid leaching, water leaching to remove the acid and then immersed in a sodium sulfite solution.

4. A synthetic brake pad material according to claim 3, characterized in that: The acid solution used in the acid leaching treatment is a 2.4-3.6wt% sulfuric acid solution.

5. The synthetic brake pad material according to claim 1, characterized in that: The friction modifier is molybdenum disulfide.

6. A synthetic brake pad material according to claim 5, characterized in that: The particle size of the molybdenum disulfide is 0.5-2.5 μm.

7. The synthetic brake pad material according to claim 1, characterized in that: The mineral fiber is basalt fiber.

8. A synthetic brake pad, characterized in that: It comprises a steel back (1) and a friction member (2) formed by solidifying the synthetic brake pad friction material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Supported sulfur, preparation method and application thereof and rubber composition

    CN110643072A

  • Friction material, composition brake shoe made of friction material and preparation method and application of composition brake shoe

    CN116396612A

  • Friction material, composite brake pad made of friction material, and preparation method and application of composite brake pad

    CN117511206A